STUDENTS FACE EXPRESSION OF HYBRID LEARNING AT STATE COLLEGE OF ISLAMIC STUDIES MANDAILING NATAL - muhammad Ari Saputra (SALEE: Study of Applied Linguistics and English Education, 2023)
This study describes students’ face expression of hybrid learning at state college of Islamic studies Mandailing Natal. The purpose of this study was to describe students' facial expressions during hybrid learning using Ekman's (2003) theory of face: surprise, fear, anger, disgust, sadness, and happiness. The teacher must determine whether or not the students understand what he is saying. Face generated interest, concentration, and perplexity (Ekman, 2003:3). This study will help teachers and lecturers understand the facial expressions made by students during the teaching process, as well as how students feel in the classroom. In this study, the descriptive method was combined with a qualitative approach. The focus of this study was on students' facial expressions while participating in hybrid learning. In hybrid learning, ten data points of facial expression were identified. The data revealed that 20% of those with surprise expressions, 10% with fear expressions, 10% with disgust expressions, 10% with anger expressions, 30% with happiness expressions, and 10% with sadness expressions. The data is presented in the form of facial expressions while the contribute to making hybrid learning. The findings of this study show that hybrid learning is ineffective in distance learning, as evidenced by students' facial expressions during the teaching process.